Conjoint impacts of continental outflows and marine sources on brown carbon in the East China sea: Abundances, optical properties, and formation processes. (15th March 2022) - Li, Hao; Qin, Xiaofei; Wang, Guochen; Xu, Jian; Wang, Lan; Lu, Da; Liu, Cheng; Zheng, Haitao; Liu, Jianguo; Huang, Kan; Deng, Congrui
Abstract: Brown carbon (BrC), as a short-lived climate forcer, is still poorly understood due to its insufficient quantification of chemical compositions, ambiguous optical properties, and complex formation mechanisms. This study firstly investigated the characteristics of BrC over a remote island of the East China Sea during the winter of 2019. Driven by the continental outflows, BrC increased 3–8 times than the clean episodes. Different from most urban studies, high water-soluble organic carbon to organic carbon (WSOC/OC) ratios (66% ± 18%) and low MS-BrC/WS-BrC ratios (methanol extracts vs. water extracts, 1.1) were observed, which resulted from the aging processes via the long-range transport over the ocean. When air masses originated from northern China with long travelling history over the ocean, aqueous phase processing promoted the formation of BrC under rich ammonium and nitrate. In contrast, air masses from eastern China travelled over less oceanic areas and were characterized of higher oxidation capacity, suggesting a dominant role of gas-phase processing in the formation of BrC. Biomass burning, fossil fuels combustion, and marine sources were apportioned as the major contributors to carbonaceous aerosols, of which marine sources accounted for more than 30%. The fractional solar absorption by BrC relative to elemental carbon in the ultraviolet range (300–400 nm) was simulated as 17.3 ± 7.51% for WS-BrC and 21.18 ± 7.97% for MS-BrC, indicating a non-negligible role of BrC in perturbating the radiative forcing in the marine atmosphere. Highlights: BrC was firstly investigated over the East China Sea during winter. BrC increased 3–8 times than clean episodes when driven by the continental outflows. High WSOC/OC ratios (66% ± 18%) and low MS-BrC/WS-BrC ratios (1.1) were observed. Marine sources contributed for more than 30% of carbonaceous aerosols. Aqueous phase process and gas-phase process promoted BrC formation.